The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ee00331b
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-grafted anion-exchange membranes: the switch from low- to high-density polyethylene leads to remarkably enhanced fuel cell performance

Abstract: Radiation-grafted HDPE-based anion-exchange membranes perform better than LDPE-based benchmarks despite exhibiting similar ex situ properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
216
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(232 citation statements)
references
References 31 publications
4
216
0
Order By: Relevance
“…[ 7 ] Varcoe and co‐workers reported that a HEMFC reaches a peak power density of 2.55 W cm −2 with an anodic metal loading of 0.6 mg PtRu cm −2 or 0.4 mg Pt cm −2 and a high‐density polyethylene‐(HDPE)‐based radiation‐grafted membrane. [ 8 ] It is obvious that the PtRu loading or Pt loading at the anode of HEMFCs is still high. For practical applications, the anodic noble metal loading has to be mitigated significantly.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Varcoe and co‐workers reported that a HEMFC reaches a peak power density of 2.55 W cm −2 with an anodic metal loading of 0.6 mg PtRu cm −2 or 0.4 mg Pt cm −2 and a high‐density polyethylene‐(HDPE)‐based radiation‐grafted membrane. [ 8 ] It is obvious that the PtRu loading or Pt loading at the anode of HEMFCs is still high. For practical applications, the anodic noble metal loading has to be mitigated significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the highest AEMFC performances reported to date are based on this fabrication method. 3,22 DMD-10 shows a maximum power density of 800 mW cm À2 (compared to DMD-5 and DMD-3), which is likely a result of the thicker membrane, leading to increased ionic resistance (42 mOhm cm 2 @ 2000 mA cm À2 ) and an earlier onset of mass transport losses. The increased mass transport losses can most probably be ascribed to the reduced water back diffusion from the anode to the cathode side caused by the thicker membrane, 12,23 since all other fabrication and operation parameters were kept the same.…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
“…8 The robustness to changes in relative humidity of the fuel cells described in this work is likely attributable to the very thin membranes, enabled by direct deposition: as motivated earlier, the use of very thin membranes is considered as key to access high performance, low power degradation as well as robust water balance between anode and cathode. 22,25 The best fuel cell performance was achieved at a relative humidity of 91/91% (68/68 C) with 1018 mW cm À2 . As shown in Fig.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, a series of three AEMFCs were assembled with AEMs prepared with irradiated ETFE-based AEI (anion-exchange ionomer) powders with the QAs benzyl-N-methylpiperidinium (MPRD), benzyltrimethylammonium (TMA), and benzyl-N-methylpyrrolidinium (MPY) showing very good performances at 60 • C [107]. However, at the same time, a study with a new high-density polyethylene-based (HDPE) radiation-grafted AEM proved that using HDPE as a precursor film directly led to enhanced performance characteristics in comparison to an ETFE one [114]. Nevertheless, the longest durability testing of an AEMFC (H 2 /O 2 -fed) was reported by Omasta et al [115] using radiation grafted ETFE films bearing benzyltrimethylammonium (BTMA) cations as the AEM.…”
Section: Energy Storage Devicesmentioning
confidence: 99%